Use of a Cirrhosis Admission Order Set Improves Adherence to Quality Metrics and May Decrease Hospital Length of Stay. (12th August 2022) - Bhavsar-Burke, Indira; Guardiola, John J.; Hamade, Nour; Gerke, Steven; Burke, Sean M.; Merrill, Katherine; Mulvey, Karalea D.; Orman, Eric S.; Fayad, Nabil
Abstract : INTRODUCTION: Quality metrics for inpatient cirrhosis management have been created to improve processes of care. We aimed to improve adherence to quality metrics by creating a novel clinical decision support (CDS) tool in the electronic health record (EHR). METHODS: We developed and piloted an alert system in the EHR that directs providers to a cirrhosis order set for patients who have a known diagnosis of cirrhosis or are likely to have cirrhosis. Adherence to process measures and outcomes when the CDS was used were compared with baseline performance before the implementation of the CDS. RESULTS: The use of the order set resulted in a significant increase in adherence to process measures such as diagnostic paracentesis (29.6%–51.1%), low-sodium diet (34.3%–77.8%), and social work involvement (36.6%–88.9%) ( P < 0.001 for all). There were also significant decreases in both intensive care and hospital lengths of stay ( P < 0.001) as well as in-hospital development of infection ( P = 0.002). There was no difference in hospital readmissions at 30 or 90 days between the groups ( P = 0.897, P = 0.640). DISCUSSION: The use of CDS in EHR-based interventions improves adherence to quality metrics for patients with cirrhosis and could easily be shared by institutions through EHR platforms. Further studies and larger sample sizes are needed to better understand its impact on additional outcome measures.